Réponses

2012-10-11T19:55:51+02:00

X(3x-3) + 5(3x-3)= 0 reponse (3x-3)(x+5) donc x= 1 ou x= -5

3x(x+6)-7(x+6)= 0 reponse (x+6)(3x-7)=0 donc x=-6 ou x=7/3

(2x+3)² - (x-5)(2x+3)=0 reponse (2x+3)(2x+3-x+5)=0 ensuite (2x+3)(x+8)=0 donc x=-3/2 ou x=-8

(4x-5)(3x+2)=2(4x-5) reponse (4x-5)(3x+2-2) donc x=5/4 ou x=0

(4x+7)(2x-3) = 5x(4x+7) reponse (4x+7)(2x-3-5x) donc x= -7/4 ou x=-1

Meilleure réponse !
2012-10-11T21:35:16+02:00

x(3x-3)+5(3x-3) = 0
3(x-1)(x+5) = 0
(x-1)(x+5) = 0
solution pour x=1 ou x= -5

3x(x+6)-7(x+6) = 0
(x+6)(3x-7) = 0
solution pour x= -6 ou x=7/3

(2x+3)² - (x-5)(2x+3) = 0
(2x+3)(2x+3-x+5) = 0
(2x+3)(x+8) = 0
solution pour x= -3/2 ou x= -8

(4x-5)(3x+2) = 2(4x-5)
(4x-5)(3x+2) - 2(4x-5) = 0
(4x-5)(3x+2-2) = 0
3x(4x-5) = 0
x(4x-5) = 0
solution pour x=0 ou x=5/4

(4x+7)(2x-3) = 5x(4x+7)
(4x+7)(2x-3) - 5x(4x+7) = 0
(4x+7)(2x-3-5x) = 0
(4x+7)(-3-3x) = 0
-3(4x+7)(1+x) = 0
(4x+7)(1+x) = 0
solution pour x= -7/4 ou x= -1

En espérant t'avoir aidé.